2021
DOI: 10.1002/1873-3468.14080
|View full text |Cite
|
Sign up to set email alerts
|

The CDC37‐HSP90 chaperone complex co‐translationally degrades the nascent kinase‐dead mutant of HIPK2

Abstract: Homeodomain-interacting protein kinase 2 (HIPK2) is a highly conserved, constitutively active Ser/Thr protein kinase that is involved in various important biological processes. HIPK2 activates itself by auto-phosphorylation during its synthesis, and its activity is mainly controlled through modulation of its expression by ubiquitin-dependent degradation. By comparing the expression of wild-type and kinase-defective HIPK2, we have recently described a novel mechanism of HIPK2 regulation that is based on prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Although client binding by HSP90 is thought to be posttranslational, some studies have reported that kinases undergo co‐translational degradation when the chaperone is inhibited (Müller et al, 2021 ; Müller & Klempnauer, 2021 ). We found that blocking translation with cycloheximide prior to HSP90 inhibition did not reduce the degradation of either c‐Src KD or Lck KD , suggesting that HSP90‐stabilization of c‐Src KD and Lck KD does not depend on active synthesis of the clients (Figure S4B ).…”
Section: Resultsmentioning
confidence: 99%
“…Although client binding by HSP90 is thought to be posttranslational, some studies have reported that kinases undergo co‐translational degradation when the chaperone is inhibited (Müller et al, 2021 ; Müller & Klempnauer, 2021 ). We found that blocking translation with cycloheximide prior to HSP90 inhibition did not reduce the degradation of either c‐Src KD or Lck KD , suggesting that HSP90‐stabilization of c‐Src KD and Lck KD does not depend on active synthesis of the clients (Figure S4B ).…”
Section: Resultsmentioning
confidence: 99%
“…Although client binding by HSP90 is thought to be post-translational, some studies have reported that kinases undergo co-translational degradation when the chaperone is inhibited 61,62 . We found that blocking translation with cycloheximide prior to HSP90 inhibition did not reduce the degradation of either c-Src KD or Lck KD , suggesting that HSP90-stabilization of c-Src KD and Lck KD from degradation occurs primarily after translation (figure S4B).…”
Section: Resultsmentioning
confidence: 99%
“…CDC37 is barely expressed in normal prostate tissue, with the highest proportion of CDC37-positive cells in moderately differentiated prostate cancer, and has been confirmed to be a HSP90 kinase-specific partner. Specific inhibition of HSP90 kinase can be achieved by blocking its interaction or directly inhibiting CDC37, and the development of small molecule inhibitors targeting HSP90-CDC37 is another effective strategy for implementing cancer treatment ( 28 , 29 ). Our data showed that miR-885-5p can affect cell proliferation by inhibiting CDC37.…”
Section: Discussionmentioning
confidence: 99%